Kajian Filsafat Pendidikan Tentang Relasi Guru dan Murid - Faelasup Faelasup (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
The teacher-student relationship is the relationship between teachers and children that occurs in the school environment. The characteristics of the teacher-student relationship are: clear goals, work on special materials, teachers as mentors, procedural, time limit, based on student activities, and discipline. The purpose of the teacher-student relationship is to develop and shape the character and civilization of a dignified nation in the context of educating the nation's life, aiming to develop the potential of students so that humans who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent and become a democratic and responsible citizen.  The purpose of this research is to know and interpret in depth the study of the philosophy of education about the teacher-student relationship This research is a type of library research where data and data sources are taken from the literature by reading, comparing, and concluding from several figures' opinions. The analysis used in this research is content analysis. Based on the results and analysis, it is concluded that the flow of progressivism philosophy argues that the teacher-student relationship system is multi-directional, but the teacher's role is only limited to facilitator, motivator and mentor. The flow of pragmatism philosophy views that the teacher-student relationship occurs well if the teacher is always in several activities such as investigation, problem solving and discovery. As for the flow of idealism, the pattern of teacher-student relations is only one-way.